FAKTOR YANG MEMPENGARUHI BELAJAR GAMBAR KONSTRUKSI BANGUNAN SISWA KELAS XI TGB DI SMK N 1 BUKITTINGGI TAHUN AJARAN 2014/2015 - 977-998, Citra Ayu Noviani (Universitas Negeri Padang, 2016)
ABSTRACT This study aims to reveal the factors that affect learning Image Building Construction (GKB) TGB XI grade students in SMK N 1 Bukittinggi with a population of TGB XI grade students who have studied GKB in the academic year 2014 / 2015. This research is descriptive quantitative and sampling techniques using Proportional Random Sampling 48 respondents , of which 25 respondents represent a class XI TGB 1 and 23 respondents from class XI TGB 2. Data were collected using a questionnaire with Likert scale consisting of five possible answers. The number of items in the questionnaire research as much as 56 point statement. The results showed that the dominant factor affecting student learning GKB is an external factor with a percentage of 54.55%. Internal factors are the most dominant influence is the motivation to learn with the percentage of 18.06%. External most dominant factor affecting student learning GKB is a family factor to the percentage of 41.18%. Keywords: Learning, Image Building Construction